theorem writeisf (F: set) (a b: nat): $ isfun F -> isfun (write F a b) $;
Step | Hyp | Ref | Expression |
---|---|---|---|
1 |
x, y e. write F a b <-> ifp (x = a) (y = b) (x, y e. F) |
||
2 |
x, z e. write F a b <-> ifp (x = a) (z = b) (x, z e. F) |
||
3 |
x = a -> (ifp (x = a) (z = b) (x, z e. F) <-> z = b) |
||
4 |
isfun F /\ (x = a /\ y = b) -> x = a |
||
5 |
isfun F /\ (x = a /\ y = b) -> (ifp (x = a) (z = b) (x, z e. F) <-> z = b) |
||
6 |
isfun F /\ (x = a /\ y = b) -> (ifp (x = a) (z = b) (x, z e. F) -> y = z <-> z = b -> y = z) |
||
7 |
y = b -> z = b -> y = z |
||
8 |
isfun F /\ (x = a /\ y = b) -> y = b |
||
9 |
isfun F /\ (x = a /\ y = b) -> z = b -> y = z |
||
10 |
isfun F /\ (x = a /\ y = b) -> ifp (x = a) (z = b) (x, z e. F) -> y = z |
||
11 |
isfun F /\ (x = a /\ y = b) -> x, z e. write F a b -> y = z |
||
12 |
~x = a -> (ifp (x = a) (z = b) (x, z e. F) <-> x, z e. F) |
||
13 |
isfun F /\ (~x = a /\ x, y e. F) -> ~x = a |
||
14 |
isfun F /\ (~x = a /\ x, y e. F) -> (ifp (x = a) (z = b) (x, z e. F) <-> x, z e. F) |
||
15 |
isfun F /\ (~x = a /\ x, y e. F) -> (ifp (x = a) (z = b) (x, z e. F) -> y = z <-> x, z e. F -> y = z) |
||
16 |
isfun F /\ (~x = a /\ x, y e. F) /\ x, z e. F -> isfun F |
||
17 |
isfun F /\ (~x = a /\ x, y e. F) -> x, y e. F |
||
18 |
isfun F /\ (~x = a /\ x, y e. F) /\ x, z e. F -> x, y e. F |
||
19 |
isfun F /\ (~x = a /\ x, y e. F) /\ x, z e. F -> x, z e. F |
||
20 |
isfun F /\ (~x = a /\ x, y e. F) /\ x, z e. F -> y = z |
||
21 |
isfun F /\ (~x = a /\ x, y e. F) -> x, z e. F -> y = z |
||
22 |
isfun F /\ (~x = a /\ x, y e. F) -> ifp (x = a) (z = b) (x, z e. F) -> y = z |
||
23 |
isfun F /\ (~x = a /\ x, y e. F) -> x, z e. write F a b -> y = z |
||
24 |
isfun F -> x = a /\ y = b \/ ~x = a /\ x, y e. F -> x, z e. write F a b -> y = z |
||
25 |
conv ifp |
isfun F -> ifp (x = a) (y = b) (x, y e. F) -> x, z e. write F a b -> y = z |
|
26 |
isfun F -> x, y e. write F a b -> x, z e. write F a b -> y = z |
||
27 |
isfun F -> A. z (x, y e. write F a b -> x, z e. write F a b -> y = z) |
||
28 |
isfun F -> A. y A. z (x, y e. write F a b -> x, z e. write F a b -> y = z) |
||
29 |
isfun F -> A. x A. y A. z (x, y e. write F a b -> x, z e. write F a b -> y = z) |
||
30 |
conv isfun |
isfun F -> isfun (write F a b) |